The relationship between the level of anti-diabetic medication adherence and fasting blood glucose levels among patients with type II diabetes mellitus at RSUD Subang - Luthpiah, Nazla; Adiutama, Novian Mahayu; Fauziah, Wardah (Program Studi Keperawatan, Politeknik Negeri Subang, 2023)
Background: Diabetes mellitus is known as the